Application of Additive Ratio Assessment (ARAS) Method for the Selection of Youth Red Cross Chairperson at SMA Negeri 1 Lebakwangi Kuningan - Bayu Pangestu; Kosim; Asep Kosasih (MASI Mandiri Edukasi, 2022)
This study aims to build a decision support system that can choose the chairman of the Youth Red Cross using the Additive Ratio Assessment (ARAS) method and to overcome the problems faced by the selection committee for the chairman of the Youth Red Cross at SMA Negeri 1 Lebakwangi Kuningan, West Java. The ARAS (Additive Ratio Assessment) method is a multi-criteria decision-making method based on ranking using the utility degree by comparing each alternative's overall index value to the optimal alternative's overall index value. The results of the research obtained are the existence of a decision support system for the election of the candidate for the chairman of the Youth Red Cross, assisting the election committee in assessing and selecting candidates for the PMR board according to the criteria. The design of a decision support system for selecting the chairman of the Youth Red Cross at SMA Negeri 1 Lebakwangi is implemented using a web-based programming language, for the predetermined assessment criteria and sub-criteria can be stored systemized, thus enabling relatively faster processing. By using this decision support system application that has been designed, the assessment and selection of candidates for the chairman of the Youth Red Cross become more accurate and more accessible because it uses computerized media so that the selection of candidates for chairman can be more neat and systematic.